THE EFFECTIVENESS OF TAI METHOD AND CROSSWORD PUZZLE IN TEACHING WRITING RECOUNT TEXT AT TENTH GRADE OF SMA NEGERI 1 GROGOL - Putra, Yoga Pratama; Setyawati, Lely; Baehaki, Imam (Jurnal Pendidikan Bahasa Inggris Proficiency, 2023)
The research is the effectiveness of TAI method and crossword puzzle media in teaching writing recount text at tenth grade SMAN 1 Grogol. The purpose of this study was to determine the effectiveness of using TAI and Crossword Puzzle methods as learning media in writing. This study uses quantitative methods in a quasi-experimental design. Sample classes at SMAN 1 Grogol are X-IIS 3 and X-IIS 4. There are 32 pupils each class. employing questionnaires, pre- and post-tests, and other data collection methods. Four students in both the experimental class and the control class met the criterion for success or earned the KKM score, according to the pre-test findings. Only 12.5% of people who take the pre-test succeed. And the post-test results revealed that 26 students in the experimental class were able to meet the success requirements, with a percentage of 81.25%. Only 12 students in the post-test class meet the success criteria, with a percentage of 37.5%. The value of Sig. (2-tailed) 0.000 represents the outcome of the independent sample test. According to the survey's findings, the majority of students chose "yes" to each of the four questions. It may be concluded that the TAI technique and Crossword Puzzle medium are effective for training class X SMAN 1 Grogol students to write recount texts.